2009
DOI: 10.1093/jxb/ern334
|View full text |Cite
|
Sign up to set email alerts
|

Co-ordinated regulation of flowering time, plant architecture and growth by FASCICULATE: the pepper orthologue of SELF PRUNING

Abstract: Wild peppers (Capsicum spp.) are either annual or perennial in their native habitat and their shoot architecture is dictated by their sympodial growth habit. To study shoot architecture in pepper, sympodial development is described in wild type and in the classical recessive fasciculate (fa) mutation. The basic sympodial unit in wild-type pepper comprises two leaves and a single terminal flower. fasciculate plants are characterized by the formation of floral clusters separated by short internodes and miniature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 51 publications
1
44
0
3
Order By: Relevance
“…Although in general the plant architecture is the sum of a varied number of physiological and genetic pathways that give rise to a unique appearance for each species (Sussex and Kerk, 2001), the simpoidal branching system (nonapical dominance) of Capsicum genus and development of unique axillary flowers is regulated by the Fasciculata gene, whose recessive (fa) expresses a certain growth with multiple flowers in the axillae (Elitzur et al, 2009). In this investigation the parents and descendants also showed sympoidal branching with development of one or two axillary flowers, this last only for the FB progenitor; and regarding to the plant size, this was affected by the internodes length expressed in plant height and leaf size (Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although in general the plant architecture is the sum of a varied number of physiological and genetic pathways that give rise to a unique appearance for each species (Sussex and Kerk, 2001), the simpoidal branching system (nonapical dominance) of Capsicum genus and development of unique axillary flowers is regulated by the Fasciculata gene, whose recessive (fa) expresses a certain growth with multiple flowers in the axillae (Elitzur et al, 2009). In this investigation the parents and descendants also showed sympoidal branching with development of one or two axillary flowers, this last only for the FB progenitor; and regarding to the plant size, this was affected by the internodes length expressed in plant height and leaf size (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Aunque en general la arquitectura de la planta es la suma de un número variado de rutas fisiológicas y genéticas que dan origen a una apariencia única para cada especie (Sussex and Kerk, 2001), el sistema de ramificación simpoidal (no dominancia apical) del genero Capsicum y desarrollo de flores axilares únicas está regulado por el gene Fasciculata, cuyo recesivo (fa) expresa un crecimiento determinado con flores múltiples en las axilas (Elitzur et al, 2009). En la presente investigación los progenitores y descendientes también mostraron ramificación simpoidal con desarrollo de una o dos flores axilares, este último solo para el progenitor FB; y en referencia al porte de la planta este fue afectado por la longitud de entrenudos expresado en la altura de la planta y tamaño de la hoja (Cuadro 3).…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Dominant and recessive forms determine the effect of these genes. More recent research has shown that the overall appearance and position of twigs is determined by a single gene in sweet pepper [1]. Such traits are called monogenic or Mendelian traits, named after Gregor Mendel (1822-1884), the founding father of genetic research.…”
Section: Introductionmentioning
confidence: 99%